“Loss and Fear”: Acculturation Stresses Leading to Depression in South Asian Muslim Immigrants in Toronto - Akram-Pall, Saadia; Moodley, Roy (Canadian Journal of Counselling and Psychotherapy, 2016)
This article explores acculturation challenges and consequent depression among South Asian Muslim immigrants in Toronto. Thirteen immigrants were interviewed about their personal settlement and the challenges and conflicts that they experienced. The data were analyzed using a grounded theory approach. Two major themes emerged: loss and fear. Recommendations are made to inform mental health professionals who work with this population. Implications for mental health practices and future research are discussed.